Letters to the editor - Gibson, Peter (Future Hosp J, 2015)
Please submit letters for the editor's consideration within 6 weeks of publication of the Future Hospital Journal. Letters should ideally be limited to 350 words, and sent by email to FHJ@rcplondon.ac.uk.